Nonlinear elliptic p(u)−Laplacian problem with Fourier boundary condition - Stanislas Ouaro; Noufou Sawadogo (Cubo, 2020)
We study a nonlinear elliptic \(p(u)-\) Laplacian problem with Fourier boundary conditions and \(L^1-\) data. The existence and uniqueness results of entropy solutions are established.